The threshold analysis of economic growth, FDI and trade on environment pollution in China using provincial panel data - Tang, Caihong; Rosland, Anitha; Yasmeen, Rizwana; Long, Yunfei (Springer, 2023)
This research aims to analyze the threshold effect (nonlinear regression) of the impact of economic growth, foreign direct investment inflow, and trade on the environmental degradation in China from 2007 to 2019 by using panel data at the province level. The results of threshold effect regression show that China’s economic growth and trade have a single threshold effect on carbon dioxide emissions, but foreign direct investment does not have any. The results reveal that when economic development increases and reaches a threshold value, its impact on carbon dioxide emissions weakens. When trade volume increases to a threshold value, its negative impact on carbon dioxide emissions strengthens. Both methods find that foreign direct investment and trade have a slightly negative relation with carbon dioxide emissions, which may indicate that in recent years of economic development, China’s technological and industrial upgrading has been decoupling foreign investment and trade from carbon dioxide emissions. Moreover, this research finds that China’s eastern provinces have reached the threshold, yet its middle and western provinces have not. Based on our empirical results, it is suggested that the Chinese government needs to pay more attention to the unbalanced economic development and environment governance between east and middle & western areas, and take measures to prevent the transfer of polluting industries from China’s developed provinces to undeveloped middle and western provinces.